Gender in climate change, agriculture, and natural resource policies: insights from East Africa - Ampaire, Edidah L.; Acosta, Mariola; Huyer, Sophia; Kigonya, Ritah; Muchunguzi, Perez; Muna, Rebecca; Jassogne, Laurence T.P. (Springer, 2020)
Gender mainstreaming was acknowledged as an indispensable strategy for achieving gender equality at the 1995 Beijing Platform for Action. Since then, governments have made substantial efforts in developing gender-responsive policies and implementation strategies. The advent of climate change and its effects, which have continued to impact rural livelihoods and especially food security, demands that gender mainstreaming efforts are accelerated. Effective gender mainstreaming requires that gender is sufficiently integrated in policies, development plans, and implementation strategies, supported by budgetary allocations. This study analyzes the extent of gender integration in agricultural and natural resource policies in Uganda and Tanzania, and how gender is budgeted for in implementation plans at district and lower governance levels. A total of 155 policy documents, development plans, and annual action plans from national, district, and sub-county/ward levels were reviewed. In addition, district and sub-county budgets for four consecutive financial years from 2012/2013 to 2015/2016 were analyzed for gender allocations. Results show that whereas there is increasing gender responsiveness in both countries, (i) gender issues are still interpreted as “women issues,” (ii) there is disharmony in gender mainstreaming across governance levels, (iii) budgeting for gender is not yet fully embraced by governments, (iii) allocations to gender at sub-national level remain inconsistently low with sharp differences between estimated and actual budgets, and (iv) gender activities do not address any structural inequalities. We propose approaches that increase capacity to develop and execute gender-responsive policies, implementation plans, and budgets.